2012
DOI: 10.1371/journal.pone.0046187
|View full text |Cite
|
Sign up to set email alerts
|

UV Filters, Ingredients with a Recognized Anti-Inflammatory Effect

Abstract: BackgroundTo explain observed differences during SPF determination using either an in vivo or in vitro method, we hypothesized on the presence of ingredients having anti-inflammatory properties.Methodology/Principal FindingsTo research our hypothesis, we studied the 21 UV filters both available on the market and authorized by European regulations and subjected these filters to the phorbol-myristate-acetate test using mice. We then catalogued the 13 filters demonstrating a significant anti-inflammatory effect w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 24 publications
3
23
0
1
Order By: Relevance
“…These findings are consistent with those from a study in mice that reported inhibition of edema, an anti-inflammatory effect, associated with topical BP-3 application (Couteau et al, 2012). To our knowledge, no studies have examined associations between parabens and inflammation in general, or CRP specifically.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with those from a study in mice that reported inhibition of edema, an anti-inflammatory effect, associated with topical BP-3 application (Couteau et al, 2012). To our knowledge, no studies have examined associations between parabens and inflammation in general, or CRP specifically.…”
Section: Discussionsupporting
confidence: 92%
“…Animal studies suggest that BP-3 is weakly estrogenic and antiandrogenic (Krause et al, 2012), but health effects related to BP-3 exposure in humans have not been studied. In in vitro studies, BP-3 has been associated with markers of oxidative stress (Gao et al, 2013; Kato et al, 2006), but findings from an animal study suggested that BP-3 may have anti-inflammatory properties (Couteau et al, 2012)…”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study revealed that acetylsalicylic acid had no effect on MS (7,8). On the other hand, homosalate suppressed the ear edema response to dinitrobenzene (9). Because NSAIDs are well-known inhibitors of cyclooxygenase (COX) (10), and COX-2 has been observed in MS lesions (11), a possible mechanism of action of the salicylates is suppression of COX.…”
Section: Discussionmentioning
confidence: 99%
“…It is known from the literature that UV filters have anti-inflammatory effects. Diethyhexyl butamido triazone and benzophenone-5, in particular, have substantial anti-inflammatory properties, which have also been reported for homosalate, benzophones, and cinnamic acid derivates [11]. Furthermore, the sunscreen agents oxybenzone and dioxybenzone have been patented as anti-inflammatory agents [12].…”
Section: Discussionmentioning
confidence: 99%